Quantifying the effects of cultivation mode and sprouting stage on tea bud morphology and chemical quality - Zhu, Wei; Yang, Jiayi; Xiao, Suqing; Hu, Wenjing; Tian, Jiamin; Zeng, Yuchen; Huang, Zhiming; Yuan, Ziyi (Frontiers in Plant Science, 2026)
While the influences of environment and genetics on plant traits are widely recognized, quantitative analysis of their relative contributions remains limited in crop systems, constraining precise environmental manipulation of agronomic traits. This study investigated the effects of cultivation mode (representing external environment) and sprouting stage (reflecting internal developmental program) on tea bud morphology and chemical quality, with particular focus on their intrinsic relationships. Through dynamic monitoring at three sprouting period across five contrasting cultivation modes in Fuliang County, Jiangxi Province, China, key morphological and chemical traits were obtained. The effects of cultivation mode and sprouting stage were assessed using linear mixed-effects models and partial ω². Results revealed a consistent developmental trend over the observed sprouting period: across all cultivation modes, bud length and number increased continuously, while width decreased, and size first declined then increased. Critically, cultivation mode had a stronger influence on bud width, number, and size (effect sizes: 0.739—0.768) than on length (0.132), which was predominantly governed by the sprouting stage (effect size: 0.812). Cultivation mode exerted a stronger effect on morphological composite traits (0.753) than on chemical composite traits (0.530). The correlations between bud length and width and between width and number shifted from positive to negative during sprouting (P < 0.05), suggesting increasing resource competition among these traits. Most importantly, no significant correlations were observed between morphological traits and chemical quality at the final sprouting stage. Based on data from this single yet harvest-critical time point, our results directly challenge the traditional belief that bud size predicts tea quality. These findings provide new insights into gene-environment interactions, phenotypic plasticity, and ecological trade-offs in agroecosystems, establishing a scientific basis for precision management strategies that simultaneously optimize tea production and quality.